Management of a radiation oncology clinic in a clean oncology hospital during the COVID-19 outbreak - Göksel, Fatih; Güzle Adaş, Yasemin (Journal of Surgery and Medicine, 2020)
Aim: COVID-19 is a disease that was declared a pandemic by the World Health Organization (WHO) in 2020. The first case in Turkey was confirmed on 11 March 2020. Since patients with cancer were reported to have a higher risk for COVID-19 infection, as an oncology hospital, we created a mini science board within our hospital. By following the advice of this science board and the permissions of the local administrators our hospital, which is the only training and research hospital that specialized in oncology in Turkey, undertook the clean hospital mission to continue cancer treatments uninterruptedly. Radiotherapy has an essential role in cancer treatment and our radiotherapy department is the biggest one in Turkey. This retrospective study aimed to constitute ideas for special issues such as pandemics by examining the workflow of our hospital’s radiation oncology clinic. Methods: The workflow of the clinic, the precautions taken, the number of treated patients and the COVID-19 positive cases were evaluated. The records of the radiation oncology clinic were used for evaluation. Results: Two-hundred forty-seven patients in March 2020 and 164 patients in April 2020 were treated in our department. None of our staff and only 3 of our patients were COVID-19 positive. Conclusion: For emergent situations like this pandemic that may occur in the future, the existence of clean hospitals is essential to continue cancer treatments uninterruptedly.